Tax Avoidance di Indonesia dan Faktor-Faktor yang Mempengaruhinya - Zainuddin Zainuddin; Muhamad Dhanutirto F. Tuwow; Anfas Anfas (IPM2KPE, 2022)
This study aims to prove the effect of Institutional Ownership, Proportion of Independent Commissioners, Audit Committee, Sales Growth, Leverage, Capital Intensity and Inventory Intensity on Tax Avoidance. The sample of this research is 188 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample selection method used was purposive sampling and obtained a sample of 30 companies. The data analysis technique used is multiple linear regression. The results of this study indicate that. Institutional ownership has no effect on Tax Avoidance, the proportion of Independent Commissioners has no effect on Tax Avoidance, the Audit Committee has no effect on Tax Avoidance, Sales Growth has no effect on Tax Avoidance, Leverage has no effect on Tax Avoidance, Capital Intensity has no effect on Tax Avoidance, and Inventory Intensity has no effect on Tax Avoidance. In conclusion, the effect on Tax Avoidance is the proportion of independent commissioners and sales growth. Keywords: Capital Intensity, Inventory Intensity, Institutional Ownership, Audit Committee, Leverage, Sales Growth, Proportion of Independent Commissioners, Tax Avoidance